STAND-UP COMEDY SEBAGAI SASTRA LISAN MODERN DI YOGYAKARTA - , Widya Putri Ryolita, Dr. Novi Kussuji I, M. Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Stand-up comedy is one type of Western cultural phenomena which has become accepted and even popular in Indonesia. Stand-up comedy is a type of oral performance which is develops over time, keeping pace with modern developments. This differs from traditional oral literature, which faithfully follows patterns and rituals established years before. In this research paper we use the aspects of oral literature as defined by Albert B. Lord, and present a descriptive understanding of modernity and the position of stand-up comedy in the oral literary canon, in order to analyze the performances. This is intended to expand the field of oral literature research into non-traditional media, as well as to prove the modernity of stand-up comedy from an orality standpoint. Analysis shows that stand-up comedy performances are performances of orality in a modern oral form. This is because stand-up comedy has grown and developed in the modern era, and as such those performing this orality have already become literate, are familiar with technology, and use it to perform and popularize stand-up comedy. Furthermore, the modern nature of stand-up comedy is demonstrated by analyzing the aspects of oral literature defined by Lord, particularly because the transmission process and performance formulas are not purely oral (as in Lordâs examples from oral poetry). One difference in the transmission process is that the performers use the media as their teacher, and the formulas used in performances are merely a collage of the comicâs fragmented memories. This is related to the themes of the performances, including the comicâs unease or need to vent, which functions to create a space for criticism or free expressions of ideas through humor. Comics often discuss common issues (particularly the youth) or contemporary news which has already received societyâs attention. This is opposed with primary orality, which is related to the past and presented through similar narrations of tales by an illiterate storyteller. Furthermore, traditional literary works tend to have traditional limits which a performance may not cross, long-standing tropes and standards which may not be abandoned.